2022
DOI: 10.1177/02692155221141395
|View full text |Cite
|
Sign up to set email alerts
|

The role of oral and pharyngeal motor exercises in post-stroke recovery: A scoping review

Abstract: Objective To analyze intervention goals, protocols, and outcome measures used for oral and pharyngeal motor exercises in post-stroke recovery. Data sources MEDLINE, EMBASE, CINAHL, PsychINFO, and Cochrane databases were searched in September 2022. Methods Studies were included if they (1) recruited post-stroke adult patients, (2) administered exercises for the oral and/ or pharyngeal muscles, and (3) reported results at baseline and post-exercise. The extracted data included intervention goals, protocols, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 70 publications
0
10
0
2
Order By: Relevance
“…Isometric lingual exercises, which involved compressing an air-filled bulb between the tongue and the hard palate, effectively improved swallowing function [ 37 ]. Additionally, facial exercises were shown to play a significant role in addressing dysphagia in acute ischemic stroke patients [ 38 ]. Another study also suggested that exercises focused on the pharynx and larynx could enhance swallowing function [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Isometric lingual exercises, which involved compressing an air-filled bulb between the tongue and the hard palate, effectively improved swallowing function [ 37 ]. Additionally, facial exercises were shown to play a significant role in addressing dysphagia in acute ischemic stroke patients [ 38 ]. Another study also suggested that exercises focused on the pharynx and larynx could enhance swallowing function [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Все найденные типы современных (описанных за последние 5 лет) логопедических методик коррекции дизартрии мы можем разделить на: информационнокомпьютерные технологии (computer-based program) [15][16][17], исследования с применением дыхательных упражнений [12,13], исследования транскраниальной магнитной стимуляции [18][19][20][21], транслингвальной стимуляции или нейромышечной электростимуляции лицевого и тройничного нервов [22][23][24], использование акупунктуры [14], различные новые типы артикуляционной гимнастики и функциональных тренировок [25][26][27][28]. Исходя из вышеперечисленных методик, можно сказать, что, повторяя тенденции в двигательной реабилитации, логопедическое сопровождение движется в направлении повышения использования различного оборудования, отмечается рост использования инвазивных методик.…”
Section: результатыunclassified
“…Движения языка стали активнее, объемнее, нормализовался тонус мышц артикуляционного аппарата [25]. В метаанализе различных методов артикуляционной гимнастики Marzouqah R. et al (26 клинических рандомизированных исследований) выявлена проблема отсутствия унификации артикуляционных упражнений, что не позволяет адекватно сравнивать результаты различных исследований [26]. В ретроспективном исследовании Oh B.M.…”
Section: артикуляционная гимнастика и функциональные тренировки (Oral...unclassified
“…Other rehabilitative treatments and physical therapy interventions for stroke patients may include music therapy, recreational therapy, and cognitive therapy [30][31][32]. The selection of interventions used will be based on the individual needs and capabilities of the patient.…”
Section: Introductionmentioning
confidence: 99%